Knee-extensor strength, symptoms, and need for surgery after two, four, or six exercise sessions/week using a home-based one-exercise program: a randomized dose–response trial of knee-extensor resistance exercise in patients eligible for knee replacement (the QUADX-1 trial). Issue 7 (July 2022) - Husted, R.S.; Troelsen, A.; Husted, H.; Grønfeldt, B.M.; Thorborg, K.; Kallemose, T.; Rathleff, M.S.; Bandholm, T.
Summary: Objective: To investigate firstly the efficacy of three different dosages of one home-based, knee-extensor resistance exercise on knee-extensor strength in patients eligible for knee replacement, and secondly, the influence of exercise on symptoms, physical function and decision on surgery. Method: One-hundred and forty patients eligible for knee replacement were randomized to three groups: 2, 4 or 6 home-based knee-extensor resistance exercise-sessions per week (group 2, 4 and 6 respectively) for 12 weeks. Primary outcome: isometric knee-extensor strength. Secondary outcomes: Oxford Knee Score, Knee injury and Osteoarthritis Outcome Score, average knee pain last week (0–10 numeric rating scale), 6-min walk test, stair climbing test, exercise adherence and "need for surgery". Results: Primary analysis: Intention-to-treat analysis of 140 patients did not find statistically significant differences between the groups from baseline to after 12 weeks of exercise in isometric knee-extensor strength: Group 2 vs 4 (0.003 Nm/kg (0.2%) [95% CI -0.15 to 0.15], P  = 0.965) and group 4 vs 6 (−0.04 Nm/kg (−2.7%) [95% CI -0.15 to 0.12], P  = 0.628). Secondary analysis: Intention-to-treat analyses showed statistically significant differences between the two and six sessions/week groups in favor of the two sessions/week group for Oxford Knee Score: 4.8 OKS points (15.2%) [1.3 to 8.3], P  = 0.008) and avg. knee pain last week (NRS 0–10): −1.3 NRS points (−19.5%) [-2.3 to −0.2], P  = 0.018. After the 12-week exercise intervention, data were available for 117 patients (N = 39/group): 38 (32.5%) patients wanted surgery and 79 (67.5%) postponed surgery. This was independent of exercise dosage. Conclusion: In patients eligible for knee-replacement we found no between-group differences in isometric knee extensor strength after 2, 4 and 6 knee-extensor resistance exercise sessions per week. We saw no indication of an exercise dose–response relationship for isometric knee-extensor strength and only clinically irrelevant within group changes. For some secondary outcome (e.g., KOOS subscales) we found clinically relevant within group changes, which could help explain why only one in three patients decided to have surgery after the simple home-based exercise intervention. Trial registration: ClinicalTrials.gov identifier: NCT02931058 . Preprint: https://doi.org/10.1101/2021.04.07.21254965 .